Electronic Resources and Collection Development, 1st edition - Lee, Sul H. (Routledge, 2020)
This book, first published in 2002, examines how the transition to electronic resources in academic libraries has impacted traditional collection development policies and practices. Nine acclaimed librarians present their perspectives on the growing trend toward digital materials acquisition that is tipping the scales in favour of ‘access’ in the ‘ownership vs. access’ debate. The book provides insights on the use of electronic resources in major research libraries from data collection by JSTOR, a leading provider of digital resources to academic libraries.